Elementary Analysis of the Communication Complexity of Divide-and-Conquer Diffie-Hellman Key Agreement Protocol - Muhammad Arzaki ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2022)
We present a rigorous elementary analysis of the communication complexity of the Divide-and-Conquer Diffie-Hellman Key Agreement Protocol (DC-DHKA). The analysis is conducted by first determining the number of transmissions in DC-DHKA and then comparing the resulting communication complexity of this protocol with other variants of Diffie-Hellman key agreement protocols that utilize regular Diffie-Hellman key, namely the ING, GDH.1, GDH.2, and GDH.3 protocols. The mathematical and numerical analyses show that the total number of bits transmitted in the DC-DHKA protocol is always fewer than those of ING, GDH.1, and GDH.2 protocols for a group of N >= 19 participants. In addition, we also prove that the total number of bits required for the entire messages’ transmissions in DC-DHKA protocol for N participants that uses the multiplicative group Fq* is log2(q) 2^(log2(N)) (log2(N) + 1) - 2.